2016
DOI: 10.3389/fmicb.2016.00886
|View full text |Cite
|
Sign up to set email alerts
|

The Chromosomal parDE2 Toxin–Antitoxin System of Mycobacterium tuberculosis H37Rv: Genetic and Functional Characterization

Abstract: Mycobacterium tuberculosis H37Rv escapes host-generated stresses by entering a dormant persistent state. Activation of toxin-antitoxin modules is one of the mechanisms known to trigger such a state with low metabolic activity. M. tuberculosis harbors a large number of TA systems mostly located within discernible genomic islands. We have investigated the parDE2 operon of M. tuberculosis H37Rv encoding MParE2 toxin and MParD2 antitoxin proteins. The parDE2 locus was transcriptionally active from growth phase til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 70 publications
6
31
1
Order By: Relevance
“…Demidenok and colleagues showed that overexpression of the VapB antitoxin prevented cells from entering the VBNC state, while overexpression of the VapC toxin induced the VBNC state (108). Similarly, overexpression of the MParE2 toxin led to a decline in culturability due to entry into the VBNC state (109). Recently, we reported that VBNC cells of Vibrio vulnificus have significantly elevated expression of several homologues of the type II toxins of RelE and HipA compared to log-phase and stationary-phase cultures (26).…”
Section: Overlapping Molecular Mechanismsmentioning
confidence: 99%
“…Demidenok and colleagues showed that overexpression of the VapB antitoxin prevented cells from entering the VBNC state, while overexpression of the VapC toxin induced the VBNC state (108). Similarly, overexpression of the MParE2 toxin led to a decline in culturability due to entry into the VBNC state (109). Recently, we reported that VBNC cells of Vibrio vulnificus have significantly elevated expression of several homologues of the type II toxins of RelE and HipA compared to log-phase and stationary-phase cultures (26).…”
Section: Overlapping Molecular Mechanismsmentioning
confidence: 99%
“…This ParE toxin was later demonstrated to inhibit E. coli DNA gyrase in vitro, and its expression in cells recapitulated a filamentous phenotype consistent with the identified in vitro inhibition (Jiang, Pogliano, Helinski, & Konieczny, ). Other reports have corroborated in vitro ParE‐mediated gyrase inhibition for chromosomally encoded toxins from Pseudomonas aeruginosa (Pa), Vibrio cholera (Vc), and Mycobacterium tuberculosis (Mt; Gupta et al, ; Muthuramalingam, White, Murphy, Ames, & Bourne, ; Yuan et al, ). The filamentous phenotype arising from ParE toxin exposure is consistent with DNA gyrase inhibition, which is stalled during the catalytic cycle, resulting in fragmented DNA that can trigger the SOS and other responses (Kreuzer, ; Reece & Maxwell, ; Williams & Schumacher, ).…”
Section: Introductionmentioning
confidence: 81%
“…The filamentous phenotype arising from ParE toxin exposure is consistent with DNA gyrase inhibition, which is stalled during the catalytic cycle, resulting in fragmented DNA that can trigger the SOS and other responses (Kreuzer, ; Reece & Maxwell, ; Williams & Schumacher, ). While there are many triggers for SOS, the filamentous phenotype has been observed upon overexpression of multiple ParE toxins for Pa, Vc, Mt, and Caulobacter crescentus (Cc; Fiebig, Castro Rojas, Siegal‐Gaskins, & Crosson, ; Gupta et al, ; Muthuramalingam et al, ; Yuan et al, ), as well as with other gyrase‐inhibiting proteins (CcdB and Fic toxins, SmbC; Dao‐Thi et al, ; De Jonge et al, ; Harms et al, ; Nakanishi, Oshida, Matsushita, Imajoh‐Ohmi, & Ohnuki, ; Sprenger et al, ; Van Melderen, Bernard, & Couturier, ) and compounds (quinolones, novobiocin; Handel, Hoeksema, Freijo Mata, Brul, & Kuile, ; Torres‐Barcelo, Kojadinovic, Moxon, & MacLean, ). Interestingly, a MazF toxin also induces filamentation and results in persister cells, but only when ciprofloxacin has also been administered to the culture (Cho, Carr, Whitworth, Johnson, & Wilson, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For protein expression and purification, all of the Escherichia coli recombinant strains were cultured in Luria-Bertani (LB) medium (Difco) under standard conditions. M. tuberculosis cultures were grown as described earlier by Gupta et al (54). All of the cultures were grown at 37°C with shaking at 180 rpm.…”
Section: Methodsmentioning
confidence: 99%